Performance analysis between PID and fuzzy logic controller in position control system of radio telescope - Mohamad Zaber, Nursaida; Ishak, Asnor Juraiza; Che Soh, Azura; Hassan, Mohd Khair (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents PID and Fuzzy Logic Controller (FLC) that allow position control of a radio telescope. To begin with, the radio telescope and controller design are shown. Its performance is observed and analysis on the percentage of error, overshoot and rise time has been conducted. Overall, the performances of both controllers are significant with error of less than 0.26%. PID controller has shown a better performance with small error while FLC demand a further enhancement in its membership functions for more significant result.